Efektivitas managemen nyeri persalinan non farmakologi dengan Deep Back Massage - Wan Anita; Lita Nafratilova; Rummy Islami Zalni (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: The birth process will be experienced by every pregnant woman. The labor process will cause pain caused by contractions that give the effect of pain which is called labor pain. Many factors influence the response to labor pain, including parity. Pain that is felt during labor can have an effect in terms of psychology, suffering, fear, and anxiety as well as the effect on the fetus to be born. Various efforts have been made to reduce labor pain, one of which is massage..Objectives: The research objective was to determine the effectiveness of labor pain management using deep back massage techniques.Methods: The method used in this study was experimental with a one group pretest-posttest design approach that focused on pain management with massage during labour. The sample of this study were 10 mothers giving birth with 4-6 openings. The research instrument used was a questionnaire containing age, gravid, history of miscarriage and Numerical Rating Scale (NRS) pain scale. This research was conducted at Ernita Midwife Independent Practice. The time for conducting the research was carried out in November-December 2021. Pain measurements were carried out before deep back massage was given and after deep back massage was given. The research instrument used was a questionnaire and data were collected by interview. Statistical test using the Wilcoxon Signed Ranks Test.Results: The results of the study describe the level of pain felt by mothers in labor before massage, the majority of severe pain is controlled by 7 respondents (70%) and the majority of labor pain after massage is mild pain by 7 respondents (70%). Massage techniques are effective in reducing pain. The results found that the average labor pain scale before being given a massage was 8.4 and decreased after being given a massage to 2.8. The act of massage for women in labor is effective in reducing labor pain. The results of the statistical test showed a significance, p <0.05.Conclusion: Effective deep back massage techniques performed on birthing mothers provide a reduction in labor pain and are highly recommended for health workers or midwives as birth attendants who can provide deep back massage for birthing mothers.